(untitled) (Jurnal Geomine, 2015)
Work efficiency is the ratio between the effective working time is used to produce at a certain time, where the more time effectively used by the tool to operate, the greater the production can be achieved. The aim of this study was to determine the production and work efficiency of pulp preparation in samplehouse. The method used is direct observations in the field, and as for the data that is needed is the data cycle time pulp preparation, preparation of pulp production data and documentations drawing activities. The calculation result obtained by the data cycle time boyd crusher (1) 6 minutes 4 seconds, boyd crusher (2) 6 minutes 3 seconds, boyd crusher (3) 6 minutes 4 seconds, CRM (3) 6 minutes 1 second, CRM (5) 6 minutes 1 second, CRM (6) 6 minutes 10 second, cycle time pulp preparation 6 minutes 4 seconds, a time delay of 1 minute 5 seconds, the production of observations is 259 in one shift, the production of pulp preparation for 15 weeks of 232 samples. From the data processing, it can be concluded that the production of pulp preparation is equal to 259 samples in one shift and work efficiency is 85%. Keywords: Sample, sample house, cycle time, pulp preparation and production.